2010
DOI: 10.1002/hbm.20989
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate activity and the self in disorders of consciousness

Abstract: The degree of consciousness in patients with DOC was correlated with neural activity in the ACC induced by self-related stimuli. Our results not only shed light on the pathophysiology of DOC, but may also suggest a useful neural, and thus diagnostic, marker of the dysfunction of consciousness in vegetative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 45 publications
(59 reference statements)
10
79
2
2
Order By: Relevance
“…The neuroanatomy of the ACC and its connections with motor control regions suggest that this brain structure acts as the neural interface for translating intentions into actions. This idea is in agreement with studies showing that restored activity in the ACC correlates with the level of responsiveness in brain-injured patients (Qin et al, 2010;Zhou et al, 2011). Our inferior parietal finding may have importance because of its functional connection with the ACC during the conscious state and because of its suggested role in movement intention and motor awareness ).…”
Section: Discussionsupporting
confidence: 93%
“…The neuroanatomy of the ACC and its connections with motor control regions suggest that this brain structure acts as the neural interface for translating intentions into actions. This idea is in agreement with studies showing that restored activity in the ACC correlates with the level of responsiveness in brain-injured patients (Qin et al, 2010;Zhou et al, 2011). Our inferior parietal finding may have importance because of its functional connection with the ACC during the conscious state and because of its suggested role in movement intention and motor awareness ).…”
Section: Discussionsupporting
confidence: 93%
“…We recently showed that this opposed functionality of the default mode and anticorrelated "extrinsic" system has a cognitive behavioral counterpart. Explicit subjective reports for increased intensity of "internal" awareness (i.e., self-related stimulus-independent processes) were related to increased connectivity in the default network, whereas increased "external" awareness scores (i.e., perception of the environment) was associated with increased connectivity in the "extrinsic" system (Vanhaudenhuyse et al, 2011), confirming the functional significance underlying the activity of both resting networks to conscious experience in health and disease (e.g., Laureys et al, 2007;Qin et al, 2010). The selection of a control condition for hypnotic state remains challenging as, a priori, no cerebral state is close to hypnotic state.…”
Section: Discussionmentioning
confidence: 58%
“…A series of studies have illustrated that intense or emotionally relevant stimuli induce higher-level activation in MCS (for review (Laureys and Boly, 2007). In the auditory modality, these studies have used presentation of meaningful stories told by a relative (Bekinschtein et al, 2004;Schiff et al, 2005) or autoreferential stimuli such as the patient's own name (Di et al, 2007;Laureys et al, 2004b;Qin et al, 2010). The latter studies, for example, show activation of midline structures (i.e., anterior cingulate/mesiofrontal and posterior cingulate/precuneus) known to be involved in internal or self-consciousness (Laureys et al, 2007).…”
Section: Insert Tablementioning
confidence: 99%
“…The latter studies, for example, show activation of midline structures (i.e., anterior cingulate/mesiofrontal and posterior cingulate/precuneus) known to be involved in internal or self-consciousness (Laureys et al, 2007). Qin et al (2010) reported a linear correlation between activation of the anterior cingulate cortex and the level of consciousness as quantified by coma recovery scores.…”
Section: Insert Tablementioning
confidence: 99%